Pengaruh Kualitas Pelayanan, Citra Merek, Komitmen terhadap Loyalitas Pelanggan Hotel Duta Palembang - Terinda, Jenika Pasya; Retno Budi Lestari (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the influence of service quality, brand image, and commitment on customer loyalty at Hotel Duta Palembang. The research employs a descriptive quantitative approach with a non-probability sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression tests. The results indicate that service quality, brand image, and commitment have a positive and significant impact on customer loyalty, both partially and simultaneously. The Adjusted R Square value of 65.8% shows that these three variables contribute significantly to customer loyalty. Hotel Duta Palembang is advised to enhance its technology-based complaint system, strengthen its brand image through unique experiences, and maintain a strong commitment to customers. This research can serve as a reference for future studies in developing strategies to improve customer loyalty in the hospitality industry.  Keyword: Service Quality, Brand Image, Commitment, and Customer Loyalty